Twenty-Year Secular Trends in Infective Endocarditis in a Teaching Hospital. (27th July 2018) - Cuervo, Guillermo; Rombauts, Alexander; Caballero, Queralt; Grau, Immaculada; Pujol, Miquel; Ardanuy, Carmen; Berbel, Dámaris; Gudiol, Carlota; Sánchez-Salado, Jose Carlos; Ruiz-Majoral, Alejandro; Sbraga, Fabrizio; Gracia-Sánchez, Laura; et al.
Abstract: Background: The purpose of this study was to analyze the secular trends of infective endocarditis in a teaching hospital between January 1996 and December 2015. Methods: We report on a single-center retrospective study of patients with left-side valve infective endocarditis. We performed an analysis of secular trends in the main epidemiological and etiological aspects, as well as clinical outcomes, in 5 successive 4-year periods (P1 to P5). Results: In total, 595 episodes of infective endocarditis were included, of which 76% were community-acquired and 31.3% involved prosthetic valves. Among the cases, 70% occurred in men, and the mean age (SD) was 64.1 (14.3) years. A significant increase in older patients (age ≥70 years) between P1 (15.332%) and P5 (51.9%; P < .001) was observed. The rate of infective endocarditis on biological prostheses also increased in the prosthetic group, accounting for 30% in P1 and 67.3% in P5 ( P < .001). By contrast, there were significant decreases in vascular and immunological phenomena over the study period, with decreases in the presence of moderate to severe valvular insufficiency (75.9% in P1 to 52.6% in P5; P < .001) and valvular surgery (43% in P1 vs 29.6% in P5; P = .006). Finally, overall mortality was 23.9%, and although it was highest in P1, it subsequently remained stable through P2 to P5 (38% in P1 to 20% in P5; P = .004). Conclusions: There has been a significant increase in infective endocarditis in older patients. The decrease in moderate to severe valve regurgitation at diagnosis could explain the stable mortality despite the increase in the mean age of patients over time.